Abstract or concrete? The impact of regional typicality and advertising appeal types on consumption intention toward geographical indication products - Wang, Dan; Xu, Yueyan; Li, Wanjun; Li, Yanjun (Frontiers in Psychology, 2024)
The essential characteristic of geographical indication products is the association of the products and their region of origin. However, consumers have different associations between the product and the region of origin (i.e., different regional typicality) for different geographical indication products. In this regard, this research aims to explore how to adopt supporting advertising appeal types to improve consumers' attitude and intention toward geographical indication products with different regional typicality. To this end, this paper proposes and tests the interaction between regional typicality and advertising appeal types on consumption intention toward products, as well as the underlying mechanism and boundary conditions of this effect. Using three studies, this research finds that the adoption of abstract (vs. concrete) appeal is more likely to enhance consumption intention toward products when the geographical indication products have high regional typicality. Also, the reverse is true when the geographical indication products have low regional typicality. Furthermore, the results show that processing fluency mediates the interaction effect. In addition, the high (low) regional typicality and abstract (concrete) appeal on consumption intention toward products are more significant in the distant (close) spatial distance condition. In this way, this research provides a new perspective for studying the consumer behavior of geographical indication products and has implications for promoting the sales of geographical indication products and enhancing the brand value of geographical indication.